Investigating single-chain structure during the crystallization process by atomic force microscopy - Wang, Dingrui; Liang, Xiaobin; Nakajima, Ken (Polymer (Guilford), 2025)
Crystalline polymers have gained significant traction in various fields owing to their exceptional thermal and mechanical properties. However, the precise mechanism underlying polymer crystallization remains a subject of ongoing debate. In this study, we employed atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS), also called nanofishing to investigate the mechanical properties, chain-level structure, and interactions of individual polymer chains, thereby shedding light on the crystallization mechanism. Through control of the crystallization temperature and time of polyethylene oxide (PEO) in solution, in conjunction with differential scanning calorimetry (DSC), we present compelling evidence that polymer crystallization begins with the folding of individual chains into cluster-like forms and the subsequent aggregation of these clusters to form larger crystalline structures. The clusters adopt chain-folding structures with lengths ranging from 7.9 to 9.1 nm at distinct crystallization temperatures. Remarkably, we observed the formation of these clusters in the initial stages, even preceding the 5-min mark. Over time, these clusters progressively aggregate and grow, ultimately leading to lamella structures. This suggests that the primary chain-folding process occurs in the early stage of crystallization, presenting a significant advancement in our understanding of the behavior of polymers at the chain level during the crystallization process. These insights hold immense value in the design and development of advanced crystal-based polymer materials. [Display omitted] •Investigating the chain-level behavior during crystallization.•Discovering the interchain and intrachain structure in the early stage of crystallization.•Polymer chains first fold to form small clusters and then aggregate to form crystals during crystallization.